Production of Bioethanol from Sugarcane Bagasse with Variations in Yeast Mass - Hery Gunawan; Eka Sri Yusmartini; Elvidiah Elvidiah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
Energy availability is an absolute requirement in national development efforts at present or in the future. The existence of limited energy sources, while the need continues to increase requires alternative sources of fossil energy. Bioethanol is one of the bioenergy which is an alternative to replace the use of fossil fuels. This research aims to obtain bioethanol by utilizing bagasse as raw material. The manufacture of bioethanol consists of several stages, among others, preparation of raw materials by drying bagasse and then mashing it to obtain bagasse with a size of 100 mesh, thermal hydrolysis process with the help of sulfuric acid solution with varying concentrations, fermentation process carried out with the help of yeast, distillation process, and content analysis. ethanol. The method used is hydrolysis with sulfuric acid. Furthermore, the hydrolysis with sulfuric acid at 150 oC for 1 hour to form a slurry. The fermentation process uses a mass variation of yeast Saccharomyces Cerevisiae with a variation of 6.75, 8.75, 11.25, 13.75, and 16.25 g  for 4 days with pH 5, room temperature and anaerobically. The best bioethanol content in the study with a mass variation of the yeast Saccharomyces Cerevisiae with a pH of 5 and a fermentation time of 4 days was 98.93% with a yield of 57.6 mLKeywords: Bagasse, Bioethanol, Saccha sromyces cereviceae, Yeast mass, Fermentation